(3NWHI aj Bi GdMQhas - (3Ydj Hf CHj WGdH GdbQTj,J (B40 (3g` s
(3ChdgG (B:s
(3bGd Ydi Hf eMeO GdJejei Yf Ydi Hf CHj WGdH Ydjge GdSdGe bGd GLJeY CUMGH QShd Gddg Udi Gddg Ydjg hSde afPcQ hCf Ci GdMQha GONd ai GdcdGe s
(3BNQgG (B:s
(3Ke bQC Ydjg GdSdGe Jdc GdOGQ GdBNQI fLYdgG ddPjf dGjQjOhf YdhkG ai GdCQV hdGaSGOGU hGdYGbHI ddeJbjf JeJ GdNWHI s
(3Vef eLehY , JQJjHgG (B: (3GdMGOi hGdYTQhfs
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs